2009
DOI: 10.1103/physrevlett.102.133202
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Positronium Formation from Helium, Argon, and Xenon

Abstract: The cross sections for the formation of positronium in the 2P state in collisions of positrons with He, Ar, and Xe atoms have been determined by measuring coincidences between the remnant ion and the Lyman-alpha photon from positronium. The maximum fractional contributions of these to the total Ps formation cross sections increase from approximately 0.06+/-0.01 in He to 0.12+/-0.04 in Ar and 0.26+/-0.09 in Xe. In the case of He, good agreement is found with a coupled-state calculation; for Ar and Xe, measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 39 publications
3
30
0
Order By: Relevance
“…Recently, there have been experimental determinations of Q Ps for the noble gases [e.g. 2,3] and the first experimental measurements of Ps formation into the 2P state (Q Ps (2P)) for He, Ar and Xe [4]. With the exception of He, there have been fewer theoretical determinations of Q Ps , however, there are a number of cross-sections for excited-state Ps formation [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been experimental determinations of Q Ps for the noble gases [e.g. 2,3] and the first experimental measurements of Ps formation into the 2P state (Q Ps (2P)) for He, Ar and Xe [4]. With the exception of He, there have been fewer theoretical determinations of Q Ps , however, there are a number of cross-sections for excited-state Ps formation [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5]. Recent experimental studies also include its formation in an excited state [6] or accompanied by ionic excitation [7]. However, whilst theoretical predictions for the differential Ps formation cross-section ( dQPs dΩ ) are available for atomic [8][9][10][11][12][13][14][15][16] and molecular [17,18] hydrogen, the noble gases [9,16,[19][20][21][22][23][24][25][26][27][28][29] Details of the experimental arrangement employed at UCL for producing a beam of Ps atoms, together with a review of recent advances, may be found in [41].…”
mentioning
confidence: 99%
“…This has motivated numerous studies of collisions in which electrons in atomic or molecular targets are captured by positrons [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. In a collision, each of the various modes into which the system under study may be fragmented is called a channel.…”
Section: Introductionmentioning
confidence: 99%